THE MONITORING OF CARBON MONOXIDE AIR POLLUTANT, AS PART OF THE AIR QUALITY MANAGEMENT. CASE STUDY: THE OLT COUNTY, ROMANIA - CONSTANTIN, Dana-Maria OPREA; TOPOR, Dan Ioan; Căpușneanu, Sorinel; BARBU, Cristian Marian; BOGAN, Elena (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
The processes that cause changes to the natural characteristics of the air have a strong dynamic; this being a reason why the environmental study must have sufficient quantitive and qualitative data, in order to meet the appropriate requirements of the spatial and temporal representation. This paper deals with issues of the air quality management in the Olt County, for the pollution indicator – carbon monoxide (CO). The paper presents the main features of this pollutant, the emission sources and the monitoring for 2014, the year with the lowest emission of CO, for the period 2008 – 2014, in terms of the annual, monthly and daily average concentrations, in relation to the causes that diminish or emphasize the values. In the end of the paper, the authors present the conclusions based on the data interpretations, provided after the monitoring of the pollution indicator – CO.